Complementary cupping effectively lowers blood pressure in hypertension - Masdalifah Pasaribu (Institute of Computer Science (IOCS), 2023)
Hypertension is a global problem that affects many countries and requires proper control to prevent complications. Cupping therapy is a nonpharmacological treatment that can help lower blood pressure in patients with hypertension. Cupping therapy is carried out by removing toxins from the body and improving blood vessel circulation so that it can have a vasodilating effect and reduce blood pressure stably in hypertensive patients. This study aims to determine the effectiveness of cupping complementary therapy in reducing blood pressure in hypertensive patients at the Cupping Clinic of Nurush Syifa Healthy House Pekanbaru in 2021. In this study, a pre-experimental method was used with a one-group pretest post-test design. The study population was all hypertensive patients, with a sample of 18 people taken using a purposive sampling technique. The results showed that there was a decrease in blood pressure in hypertensive patients after undergoing cupping therapy. Data analysis using the Wilcoxon test showed a p-value of 0.001 (<0.05), indicating a significant difference between blood pressure before and after the intervention. In conclusion, cupping therapy can be an alternative nonpharmacological therapy that is effective in reducing blood pressure in hypertensive patients. The results of this study are expected to provide information and benefits for the community and the clinic so that cupping therapy can be better recognized and considered as a way to control blood pressure in hypertensive patients.